Engineering the world stories from the first 75 years of Texas Instruments - Pirtle, Caleb (Southern Methodist Univ. Press, 2005)
"This volume celebrates the can-do, risk-taking, innovative pioneers of Texas Instruments from the company's inception as a tiny geophysical exploration business deeply entrenched in the oilfields of the Southwest to its status today as one of the world's leading electronics companies. In photographs and anecdotes, the book tells TI's history of innovation in products and technologies, as well as in its management philosopies, personnel development, and business processes. Many of TI's customers - from IBM in the 1950s to current major telecommunications companies - have benefited from TI's technological breakthroughs." "For seven-and-a-half decades, TI has been a leader in world-changing innovations, including the first commercial silicon transistors, the first integrated circuits, and the first electronic hand-held calculator. Today, TI is at the forefront of digital signal processing and analog technologies, the semiconductor engines of the Internet age." "TIers are currently working on solutions for large global markets such as wireless and broadband access, and for a variety of emerging markets such as digital projection systems and digital audio." "The seventy-five vignettes making up this history paint a picture of TI and its people, providing a window into a corporate culture that fosters the creativity and mental toughness needed to compete in the world semiconductor market. The stories, in addition, show TI's staunch sense of fiscal responsibility, civic mindedness, and high ethical standards in its business practices."--BOOK JACKET.